Petal abscission in roses is associated with the activation of a truncated version of the animal PDCD4 homologue, RbPCD1 - Singh, Priya (Plant science : an international journal of experimental plant biology, 2019)
Copyright © 2019 Elsevier B.V. All rights reserved.